E-Tailing Consumer Adoption in The Indonesian Fashion Industry: The Role of Technology Acceptance Model - Aldi Ramdhani Fahlevi Deisti; Ira Siti Sarah; Ivon Sandya Sari Putri; Leni Nur Pratiwi (Jurnal Riset Bisnis dan Investasi, 2019)
The retail web system, also known as e-tailing, has utilized by many national and multinational fashion companies in Indonesia. However, many consumers are hesitated to adopt this new kind of transaction channel. This study aims to test consumers’ adoption of e-tailing in the Indonesian fashion industry using technology acceptance model (TAM), i.e. perceived ease of use (PEU), perceived usefulness (PU), and attitude towards using (ATU). A quantitative approach was used in this study. The web user of 169 respondents was asked to fill in a questionnaire. The collected data was then analysed using structural equation modelling (SEM). The result finds e-tailing adoption is strongly impacted by perceived ease of use, perceived usefulness, and attitude towards using. This study suggests sales manager hear consumers' needs and behaviour when they go shopping online.